2016
DOI: 10.14507/epaa.24.1739
|View full text |Cite
|
Sign up to set email alerts
|

Exploring quality programs for English language learners in charter schools: A framework to guide future research

Abstract: Although there has been a great deal of debate about the effectiveness of charter schools in the research literature, there has been surprisingly little attention paid to English language learners (ELLs) in charter schools. Moreover, the charter school research has predominantly focused on whether or not charter schools are effective rather than how or why high-performing charter schools work, particularly for ELLs. We contend that researchers must expand their focus beyond access and achievement and begin to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…In their mixed-method study of Latinx and non-Latinx parents whose children were enrolled in a diverse charter school in Indianapolis, Indiana, Mavrogordato and Stein (2016) found that while both sets of parents conducted a multi-stage search process and had similar criteria for evaluating schools, Latinx parents relied more heavily on social networks for obtaining school information, and rarely used additional tools-either because of linguistic or technological barriers, or because they were unaware of their existence. The use of all-English printed marketing, digital materials, and monolingual English staff has (perhaps unsurprisingly) been cited as a significant and widespread exclusionary measure that prevents ELs from enrolling in charter schools (ACLU, 2017;Ayscue et al, 2017;Garcia & Morales, 2016;Mommandi & Welner, 2018). It is also possible that there are differences in English proficiency between ELs enrolled in charters and those in district schools (Buckley & Sattin-Bajaj, 2011).…”
Section: Charter Schoolsmentioning
confidence: 99%
“…In their mixed-method study of Latinx and non-Latinx parents whose children were enrolled in a diverse charter school in Indianapolis, Indiana, Mavrogordato and Stein (2016) found that while both sets of parents conducted a multi-stage search process and had similar criteria for evaluating schools, Latinx parents relied more heavily on social networks for obtaining school information, and rarely used additional tools-either because of linguistic or technological barriers, or because they were unaware of their existence. The use of all-English printed marketing, digital materials, and monolingual English staff has (perhaps unsurprisingly) been cited as a significant and widespread exclusionary measure that prevents ELs from enrolling in charter schools (ACLU, 2017;Ayscue et al, 2017;Garcia & Morales, 2016;Mommandi & Welner, 2018). It is also possible that there are differences in English proficiency between ELs enrolled in charters and those in district schools (Buckley & Sattin-Bajaj, 2011).…”
Section: Charter Schoolsmentioning
confidence: 99%
“…Other studies focused on diverse charter schools have found that many use similar practices to promote diversity (Jabbar & Wilson, 2018; Villavicencio, 2016). Other charter school practices that support diversity include forging connections with community organizations, using multilingual messaging, and providing culturally responsive information to families (Garcia & Morales, 2016; Villavicencio, 2016). At the same time, some diverse districts and schools have used messaging and made programmatic changes that cater to White families, in effect commodifying families of color and/or linguistically diverse families rather than centering the needs and experiences of these families (Cucchiara, 2013; Palmer, 2010; Posey-Maddox, 2014; Turner, 2020; Woody, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have developed frameworks examining the roles of different levels of government in education broadly (Mitra, 2018;Spillane, 1998;Wirt & Kirst, 2009). With regard to EL education, some have focused on specific policy elements, such as assessment (Lacelle-Peterson & Rivera, 1994), charter schools (Garcia & Morales, 2016), or language development programs (Mitchell, Destino, Karam, & Colón-Muñiz, 1999). In this paper we draw upon theoretical state education policy frameworks (Mitra, 2018;Wirt & Kirst, 2009) as well as en situ state English learner education frameworks in select states (California Department of Education [CDE], 2017; New York State Department of Education [NYSDE], 2014) to create a conceptual framework for state EL education policy.…”
Section: Conceptual Policy Frameworkmentioning
confidence: 99%